Presidential Authority to Grant Abolition under the 1945 Constitution of Indonesia - Hendra Vranata; Siti Marwiyah; Fathul Hamdani (Faculty of Law, Merdeka University Surabaya, Indonesia, 2026)
This study aims to analyze the President’s authority to grant abolition as regulated under Article 14 paragraph (2) of the 1945 Constitution of the Republic of Indonesia and to examine its implications for the rule of law and the principle of checks and balances within the Indonesian constitutional system. Abolition constitutes a distinctive form of state clemency because it terminates criminal prosecution prior to a final court judgment, thereby directly intersecting with judicial independence. This research employs a normative juridical method using statutory, conceptual, and case approaches, with the granting of abolition to Tom Lembong serving as a case study. The results show that, normatively, the President’s authority to grant abolition is constitutionally valid; however, the absence of comprehensive statutory regulation creates legal uncertainty and weakens normative safeguards. Furthermore, the findings reveal that the supervisory role of the House of Representatives tends to function procedurally rather than substantively, thereby reducing the effectiveness of the checks and balances mechanism. Accordingly, this study concludes that strengthening the normative framework and oversight mechanisms is essential to ensure that the exercise of abolition remains consistent with the rule of law, substantive justice, and the independence of Indonesia’s criminal justice system.